Explaining the effects of processing on the electrical properties of PEDOT: PSS - Reenen, Stephan van; Scheepers, Max; Ruit, Kevin van de; Bollen, Dirk; Kemerink, Martijn (Organic electronics, 2014)
By simultaneously measuring the Seebeck coefficient and the conductivity in differently processed PEDOT:PSS films, fundamental understanding is gained on how commonly used processing methods improve the conductivity of PEDOT:PSS. Use of a high boiling solvent (HBS) enhances the conductivity by 3 orders of magnitude, as is well-known. Simultaneously, the Seebeck coefficient S remains largely unaffected, which is shown to imply that the conductivity is improved by enhanced connectivity between PEDOT-rich filaments within the film, rather than by improved conductivity of the separate PEDOT filaments. Post-treatment of PEDOT:PSS films by washing with H2SO4 leads to a similarly enhanced conductivity and a significant reduction in the layer thickness. This reduction strikingly corresponds to the initial PSS ratio in the PEDOT:PSS films, which suggests removal and replacement of PSS in PEDOT:PSS by HSO4− or SO42− after washing. Like for the HBS treatment, this improves the connectivity between PEDOT filaments. Depending on whether the H2SO4 treatment is or is not preceded by an HBS treatment also the intra-filament transport is affected. We show that by characterization of S and σ it is possible to obtain more fundamental understanding of the effects of processing on the (thermo)electrical characteristics of PEDOT:PSS.
Gesehen am 04.12.2019